Reversed-phase high-performance liquid chromatographic method development and validation for allyl isothiocyanate estimation in phytosomes of Brassica nigra extract - Surendra S Agrawal; Tapasya Yallatikar; Pravina Gurjar (Wolters Kluwer Medknow Publications, 2019)
A simple, specific, accurate, precise, and robust reverse-phase high-performance liquid chromatographic method has been developed and validated for the estimation of allyl isothiocyanate (AITC) in phytosomes of black mustard extract (Brassica nigra). The method was validated with respect to specificity, linearity, accuracy, precision, and robustness. The linearity was achieved over a range of 10-18 μg/mL and regression coefficient was obtained 0.9961. Accuracy of chromatographic method was evaluated by standard addition method; percentage recovery attained was 97.07 ± 0.008-103.66 ± 0.013. Relative standard deviation for intraday and interday precision was 0.02% and 0.22%, respectively. The limit of detection and limit of quantification of the AITC were found to be 0.0043 μg/mL and 0.01324 μg/mL, respectively. This result shows that the method was well validated. In the present study, the AITC content was found 0.0009% ± 0.014% in black mustard. This study reveals that the proposed high-performance thin-layer chromatography method is accurate, fast, and cost-effective for the routine estimation of AITC in the phytosome formulation.